PENATALAKSANAAN HOLISTIK DISPEPSIA FUNGSIONAL PADA WANITA USIA 21 TAHUN DENGAN MELALUI PENDEKATAN DOKTER KELUARGA - Redina Andini; Aila Karyus (Medula, 2022)
Dyspepsia fungsional is health problems that are often encountered in daily practice and are diseases with a large number of cases in Indonesia. Family doctor services play an important role as a treatment approach for patients because it applies as a help of healing, health promotions, and preventing diseases. The family doctor approach includes patient centred, family approach strategies, and community oriented. Important role in reducing the incidence and mortality of dyspepsia, as well as increasing the cure rate. Patients must know about their disease and have the awareness and motivation to complete treatment and lifestyle modifications so that treatment goals can be achieved. The study is a case report. Primary data were obtained through history taking, physical examination and home visits. Secondary data were obtained from the patient's medical record at the Puskesmas. Assessment is carried out based on a holistic diagnosis from the beginning, process, and end of the study quantitatively and qualitatively. A patient with complaints of heartbrun since 1 days before going to the Puskesma. Patient complains of abdominal discomfort such as feeling of bloating and pain in the form of stinging in the middle of abdomen and burning sensation in the pit of stomach. Another complaint that is felt  is feeling nauseous, vomiting and no appetite. In this case, diagnosis and treatment have been carried out according to the latest theory and journals. After the intervention, there was a decrease in clinical symptoms and an increase in the knowledge of patients and their families. patient Patients diagnosed with dyspepsia fungsional was in accordance with the theory from several guidelines and journals, there was a change in knowledge of the patient and his family after an intervention based on Evidence-Based Medicine which was patient-centred and family approach.